Kansas and Kansans in World War I : service at home and abroad - Watson, Blake A., 1956- (Lawrence, Kansas : University Press of Kansas, 2024)
"According to the American Battle Monuments Commission, approximately 80,000 Kansans served in the US armed forces during World War I. In Kansas and Kansans in World War I, Blake Watson helps readers understand how World War I affected Kansas and its residents, and how Kansans in turn had an impact on the outcome of the Great War. Through thorough and extensive use of letters, newspapers, and other documents, Watson brings individual soldiers' service to life, using their own words to describe their attitudes and experiences. Watson also looks at Kansans' service and support on the home front, chronicling Kansans' participation in initiatives such as Liberty Loan bonds, newspapers' publication of military service honor rolls and soldiers' letters from abroad, and the xenophobia and hysteria that confronted Mennonites--who were pacifists--and German Americans"--
1916 -- The President Comes to Topeka: Woodrow Wilson and the "Preparedness" Debate -- Oskaloosa Forms a Company in the National Guard -- The Kansas National Guard at the Mexican Border -- "Today we stand behind the nation's chosen leader": Kansas Supports War With Germany -- The Army Draft and "Fatal Number 258" -- Kansas "Rainbow" Guardsmen: The 117th Ammunition Train of the 42nd Division -- Camp Funston: Whites and Blacks Form the 89th and 92nd Divisions -- Camp Doniphan: Kansas and Missouri Guardsmen Form the 35th Division -- 1917 -- Kansas Home Front: Support, Suppression, and Suspicion -- First in France: Charles Orr, Clyde Grimsley, and Frank Cadue of the 1st Division -- Victory at Cantigny: Charles Avery, Harry Martin, and Clarence Huebner of the 1st Division -- Belleau Wood: The Holton Marine Band and James Harbord of the 2nd Division -- Rocks of the Marne: Ulysses Grant McAlexander and Thomas Reid of the 3rd Division -- Death in the Trenches: Company B and the Vosges Mountains -- St. Mihiel and the 89th Division: September 12, 1918 -- Meuse-Argonne and the 35th Division: September 26 and 27, 1918 -- Meuse-Argonne and the 35th Division: September 28, 29, and 30, 1918 -- Meuse-Argonne and the 89th Division: November 1 and 2, 1918 -- Black Kansas Soldiers: Fighting Germans and Segregation -- Medals of Honor: John Balch, Erwin Bleckley, George Mallon, and George Robb -- 1919-2024 -- Kansas Home Front: Distrust, Coercion, and Influenza -- Prisoners of War and the YMCA: Clyde Grimsley, Melvin Dyson, and Conrad Hoffman -- The Kansas Home Front after the War: Joy, Uncertainty, Anger, and Remembrance -- The Boys of Company B: Davis, Segraves, Nichols, and Gutschenritter.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on October 29, 2024).
JSTOR
Keywords: Kansas. -- National Guard -- History -- 20th century; World War, 1914-1918 -- Kansas; World War, 1914-1918 -- Social aspects -- Kansas; World War, 1914-1918 -- War work -- Kansas; World War, 1914-1918 -- Regimental histories -- United States; Kansas -- Biography; Kansas -- History, Military -- 20th century; Guerre mondiale, 1914-1918 -- Kansas; Guerre mondiale, 1914-1918 -- Participation des civils -- Kansas; Guerre mondiale, 1914-1918 -- Histoire des unités -- États-Unis.; Kansas -- Histoire militaire -- 20e siècle.; Guerre mondiale, 1914-1918 -- Aspect social -- Kansas; Kansas -- Biographies; HISTORY / Wars & Conflicts / World War I; Electronic books